THE EFFECT OF SCIENTIFIC APPROACH TO THE ACTIVITY OF LEARNING STUDENTS IN SMPN 25 TANGERANG CITY - Sanyo Saputra; Hendro Prasetyono (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2020)
The purpose of this study is to find out how significant a significant level of scientific influence on student activity. The school which is the object of this research is SMP Negeri 25 Kota Tangerang on Jl. Inpres Raya RT. 003/004 Kel. Gaga Kec. Larangan Tangerang City. The method used in this study is to use t-test testing with the comparative hypothesis testing of two samples to assess whether the effect of an action on behavior or to test whether there is an effect of that action between the Scientific Approach and Student Activity. After the authors conducted t-test testing by testing the comparative hypotheses of two samples. Testing using t-test correlates with the right side test because the alternative hypothesis (Ha) sounds better. Hypothesis testing obtained t-hitung -15.637 and ttabel at position 1.668 which means that there is a high influence of scientific application on the activeness of students in social studies class VIII at SMP Negeri 25 Kota Tangerang